Where are the female composers? Evidence on the extent and causes of gender inequality in music history - Karol Jan Borowiecki; Martin Hørlyk Kristensen; Marc T. Law (European Historical Economics Society (EHES), 2024)
Ludwig van Beethoven, Johann Sebastian Bach, and Frédéric Chopin are household names, but few will recognize Francesca Caccini, Elisabeth Lutyens or Amy M. Beach, who are among the top-10 female composers of all time. Why are female composers overshadowed by their male counterparts? Using novel data on over 17,000 composers who lived from the sixth to the twentieth centuries, we conduct the first quantitative exploration of the gender gap among classical composers. We use the length of a composer's biographical entry in Grove Music Online to measure composer prominence, and shed light on the determinants of the gender gap with a focus on the development of composers' human capital through families, teachers, and institutionalized music education. The evidence suggests that parental musical background matters for composers' prominence, that the effects of teachers vary by the gender of the composer but the effects of parents do not, and while musician mothers and female teachers are important, they do not narrow the gender gap in composer prominence. We also find that the institutionalization of music education in conservatories increases the relative prominence of female_composers.
Keywords: I23; J16; J24; N30; Z11; 330; gender gap; human capital; music education; music history; studentteacher interactions; conservatories